High-performance protocol for ultra-short DNA sequencing using Oxford Nanopore Technology (ONT). - Lukas Žemaitis; Rūta Palepšienė; Simonas Juzėnas; Gediminas Alzbutas; Pierre-Yves Burgi; Thomas Heinis; Jérôme Charmet; Silvia Angeloni Suter; Martin Jost; Renaldas Raišutis; Friedrich Simmel; Ignas Galminas (PLoS ONE)
In recent years, Oxford Nanopore Technologies (ONT) has gained substantial attention across various domains of nucleic acid research, owing to its unique advantages over other sequencing platforms. Originally developed for long-read sequencing, ONT technology has evolved, with recent advancements enhancing its applicability beyond long reads to include short, synthetic DNA-based applications. However, sequencing short DNA fragments with nanopore technology often results in lower data quality, likely due to the absence of protocols optimised for these fragment sizes. To address this challenge, we refined the standard ONT library preparation protocol to improve its performance for ultra-short DNA targets. By utilising the same core reagents required for conventional ONT workflows, we introduced targeted alterations to enhance compatibility with shorter fragment lengths. We then benchmarked these adjustments against libraries prepared using the standard ONT protocol. Here, we present a comprehensive, step-by-step protocol that is accessible to researchers of various technical expertise, facilitating high-quality sequencing of ultra-short DNA fragments. This protocol represents a significant improvement in sequencing quality for short DNA sequences using ONT technology, broadening the range of possible applications.